PERAN POSYANDU EDELWAYS DALAM UPAYA PENANGANAN STUNTING DI DESA GROGOL KECAMATAN TULANGAN KABUPATEN SIDOARJO - Nur Indah Irsanti; Isnaini Rodiyah (Journal Publicuho, 2025)
As a national commitment to enhance human resource quality, handling stunting is a major concern in health development. This research seeks to outline and assess the role of the Edelways Integrated Health Post (Posyandu) in stunting management efforts using the role theory by Jim Ife and Frank Tesoriero (2016) through facilitator, educator, representative, and technical roles, while also identifying obstacles to program implementation at the field level. Data were obtained through observation, interviews, and documentation, then analysed descriptively and qualitatively. The results findings indicate a disparity between the ideal role of Posyandu and its implementation, characterised by low participation of toddlers in growth monitoring, lack of cadre activity, uneven implementation of supplementary feeding programs, and limited nutrition education. On the other hand, inconsistent aspects of recording development data and nutritional monitoring also hamper early detection of stunting cases. In light of these outcomes, this study highlights the necessity of strengthening cadre capacity, equalising resources, and increasing community involvement as key strategies to optimise the role of Posyandu in reducing stunting prevalence in rural areas.